**Algebra Formula:**

- (a + b)
^{2}= a^{2}+ 2ab + b^{2} - (a − b)
^{2}= a^{2}− 2ab + b^{2} - a
^{2}+ b^{2}= (a + b)^{2}− 2ab - a
^{2}+ b^{2}= (a − b)^{2}+ 2ab - (a + b)
^{3}= a^{3}+ b^{3}+ 3ab(a + b) - (a − b)
^{3}= a^{3}− b^{3}− 3ab(a − b) - a
^{3}+ b^{3}= (a + b)^{3}− 3ab(a + b) - a
^{3}− b^{3}= (a − b)^{3}+ 3ab(a − b) - a
^{2}− b^{2}= (a + b)(a − b) - a
^{3}− b^{3}= (a − b)(a^{2}+ ab + b^{2}) - a
^{3}+ b^{3}= (a + b)(a^{2}− ab + b^{2}) - a
^{4}– b^{4}= (a^{2}– b^{2})(a^{2}+ b^{2}) = (a + b)(a + b)(a^{2}+ b^{2}) - a
^{4}+ b^{4}= (a^{2}+ b^{2})^{2}– 2a^{2}b^{2}= (a^{2}+ √2ab + b^{2})(a^{2}– √2ab + b^{2}) - a
^{5}+ b^{5}= (a + b)(a^{4}– a^{3}b + a^{2}b^{2}– ab^{3}+ b^{4}) - a
^{5}– b^{5}= (a – b)(a^{4}+ a^{3}b + a^{2}b^{2}+ ab^{3}+ b^{4}) - a
^{n}− b^{n}= (a − b)(a^{n−1}+ a^{n−2}b + a^{n−3}b^{2}+ ··· + b^{n−1}n−1) - (a + b + c)
^{2}= a^{2}+ b^{2}+ c^{2}+ 2(ab + bc + ca) - a
^{3}+ b^{3}+ c^{3}– 3abc = (a + b + c)(a^{2}+ b^{2}+ c^{2}– ab – bc – ca) - If a + b + c = 0, then the above identity reduces to a
^{3}+ b^{3}+ c^{3}= 3abc

- Rate Formulas
- Inequalities
- Root Formula
- Fractions Formula
- Arithmetic Progression
- Summations
- Polynomial formulas
- Exponentiation Formulas
- Logarithm
- Complex Numbers Formulas
- Complex plane
- Euler’s Formula

We provide few shortcut tricks on this topic. Please visit this page to get updates on more Math Shortcut Tricks. You can also like our facebook page to get updates.

If You Have any question regarding this topic then please do comment on below section. You can also send us message on facebook.

I really enjoyed this page . thanx

Geometry ka trick and salb bhejdijiye

Can you tell me the site for English Language preparation notes

Sir bht axcha h ye pd kr bht mja aya

But khub